Broadband and high-efficiency of garnet-typed ceramic dielectric resonator antenna for 5G/6G communication application. Issue 18 (15th September 2022) - Jiang, Yu; Liu, Huan; Muhammad, Raz; Luo, Xinjiang; Song, Kaixin; Mao, Minmin; Sun, Shikuan; Bafrooei, Hadi Barzegar; Taheri-Nassaj, Ehsan; Iqbal, Yaseen; Sun, Rong; Wang, Dawei
Abstract: Garnet-typed ceramics of Y3 Mg1- x Mn x Al3 SiO12 (0 ≤ x ≤ 0.2) have been synthesized using the traditional solid-state reaction method. The optimal microwave dielectric properties ( ε r = 10.73, Q×ƒ = 62, 824 GHz, τ f = −34.8 ppm/°C) are obtained for Y3 Mg0.9 Mn0.1 Al3 SiO12 ( x = 0.1) sintered at 1575 °C for 5h. A millimeter-wave dielectric resonator antenna is designed and fabricated using Y3 Mg0.9 Mn0.1 Al3 SiO12 as a dielectric unit due to its excellent characteristics of low dielectric constant and high Q×ƒ . The designed DRA resonates at 24.94 GHz with a bandwidth ∼2.20 GHz (S 11 < −10 dB). The simulated gain and efficiency are 6.64 dBi and 91.08%, respectively. The results indicate that the Y3 Mg0.9 Mn0.1 Al3 SiO12 ceramic has a potential application as an antenna for the 5G/6G millimeter wave frequency band.